COMPLIANCE WITH INTERNATIONAL STANDARDS AND NATIONAL LEGISLATION IN THE FIELD OF CIVIL LEGAL PROTECTION OF INTELLECTUAL PROPERTY OBJECTS (TAMADDUN NURI JURNALI, 2025)
The article examines the compliance of Uzbekistan's national legislation with international standards in the field of civil law protection of intellectual property objects. Within the framework of the study, the degree to which the requirements of international documents such as the Bern Convention, the TRIPS Agreement, and the WIPO Agreement are reflected in the civil legislation of Uzbekistan is analyzed.